The Mysterious Mr Bigstain and Price Pause the Miloslav Svandrlik Prize - Novotny, Vladimir (Bohemica Olomucensia, 2024)
In 2012, under the auspices of the Writers' Association, the Prize for Humorous Literature was established, named after the popular representative of this genre, Miloslav Svandrlik (1932-2009). Initially, it was awarded annually, but its rules and especially the composition of the individual juries have changed. Eventually, there was even a "price pause", with the year relating to books published in 2021 being initially omitted and then merged with the following year. The consequences of this "price pause" are summarised in a framework with reference to the books by the pseudonymous Sigi Bigstain, who created a humorous trilogy about the fate of the contemporary Svejk, representing the grandson of the good soldier, from the pen of Jaroslav Hasek.
Keywords: Miloslav Svandrlik Prize; Writers' Association; humoristic literature; Jaroslav Hasek; Medius; Sigi Bigstain; Magnesia Litera